2015
DOI: 10.3390/jfmk1010030
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Foot Shape after Long-Distance Running

Abstract: Changes in foot shape during long-distance running may lead to alteration in shoe fit. However, little information is available on changes in foot shape following long-distance running. The purpose of this study was to assess changes in foot shape in experienced runners after a single long-distance run. Data from the right feet of 21 subjects were obtained using a foot scanner before and after running 35 km on an asphalt road. After the run, the dorsal height, navicular height, and arch height ratio were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…The scanning and analysis procedure were based on previous studies which reported transient changes in the foot shapes after LDR using the same system. 2,3 The foot was scanned both in a sitting and standing positions. A laser scanner moved around the foot in an oval trajectory, measuring the foot dimensions and the anatomical marker positions based on laser line triangulation with high accuracy.…”
Section: Measurements Of Foot Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scanning and analysis procedure were based on previous studies which reported transient changes in the foot shapes after LDR using the same system. 2,3 The foot was scanned both in a sitting and standing positions. A laser scanner moved around the foot in an oval trajectory, measuring the foot dimensions and the anatomical marker positions based on laser line triangulation with high accuracy.…”
Section: Measurements Of Foot Dimensionsmentioning
confidence: 99%
“…A laser scanner moved around the foot in an oval trajectory, measuring the foot dimensions and the anatomical marker positions based on laser line triangulation with high accuracy. 2,3 After the scanning, foot length, dorsal height, and navicular height were obtained. The arch height ratio was calculated as the navicular height normalized to the foot length.…”
Section: Measurements Of Foot Dimensionsmentioning
confidence: 99%
“…The included studies originated from 17 different countries: China ( n = 41) [4, 11, 30–68], Japan ( n = 6) [16, 44, 69–72], Germany ( n = 4) [13, 73–75], Romania ( n = 3) [8, 76, 77], South Korea ( n = 3) [78–80], Spain ( n = 3) [22, 81, 82], United States ( n = 3) [83–85], Italy ( n = 3) [20, 21, 86], India ( n = 2) [5, 87], Malaysia ( n = 2) [3, 88], New Zealand ( n = 2) [35, 62], Australia ( n = 2) [89, 90], Belgium ( n = 2) [18, 91], United Kingdom ( n = 2) [92, 93], Canada ( n = 1) [94], Iran ( n = 1) [9], Russia ( n = 1) [47], Slovenia ( n = 1) [95], and Sweden ( n = 1) [75]. Several study designs were utilised in the literature, these included: 51 comparisons of mean differences between groups [3, 5, 8, 9, 22, …”
Section: Resultsmentioning
confidence: 99%
“…Several study designs were utilised in the literature, these included: 51 comparisons of mean differences between groups [3, 5, 8, 9, 22, 30-35, 38-41, 43-45, 47-50, 52-62, 66, 68, 70, 72, 75-78, 80, 83, 85-89, 93-95], 20 cluster/ principal component analyses [5,11,13,16,18,31,32,38,42,51,58,63,64,68,73,79,82,85,87,90], 14 reliability studies [20-22, 34, 37, 39, 48, 49, 53, 75, 78, 88, 90, 91], 10 validation studies [20,21,39,40,46,48,53,65,78,81], one correlation study [33], one comparison of distributions between groups [92], one regression analysis [87], and 11 repeated measures studies were reported, which were grouped into three subcategories; seven studies reported the effect of different loading conditions [4,22,36,39,74,84,90], three reported changes before/after exercise [62,69,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Running biomechanics influences the foot structure. Following long-distance running, foot arch and dorsal height reduce over a week and may take more than a week to return to pre-run profiles and has been linked with increased plantar loadings in the medial foot (metatarsals and arch) ( Fukano and Iso, 2016 ; Fukano et al, 2018 ; Mei et al, 2018 ). These changes could affect the perceived comfort of the running footwear and contribute to running-related injuries ( Cowley and Marsden, 2013 ; Hollander et al, 2018a ).…”
Section: Foot Morphology Shape and Posture In Running Activitiesmentioning
confidence: 99%